Dropped calls in global system for mobile communication (GSM) network / Nik Mahmood Murtadza Ismail - Ismail, Nik Mahmood Murtadza (2017)
The objective of this project is to study and analyze the dropped calls in GSM network. Dropped call is major indicator of the quality of the mobile network.